Post-marketing safety surveillance of tofacitinib over 9 years in patients with psoriatic arthritis and rheumatoid arthritis - Burmester, GR; Coates, LC; Cohen, SB; Tanaka, Y; Vranic, I; Nagy, E; Lazariciu, I; Chen, A-S; Kwok, K; Fallon, L; Kinch, C (Springer Nature, 2023)
Introduction: The safety of tofacitinib in psoriatic arthritis (PsA) and rheumatoid arthritis (RA) has been demonstrated in clinical studies of ≤ 4 and 9.5 years, respectively. Post-marketing surveillance (PMS) data for tofacitinib from spontaneous and voluntary adverse event (AE) reports have been published for RA, but not PsA. To inform the real-world safety profile of tofacitinib in PsA, we evaluated AE reports submitted to the Pfizer safety database (including RA data for context).